Utilization of Canva Application in Social Knowledge Lessons - Yuswandi, Yuswandi; Fiidznillah, Rizki; Purnomo, Jumah (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. At present, the use of this Canva application in Social Science learning can be used as a means of learning media on the use of technology as an easy learning medium. Purpose. This article is an activity to provide insight to students at Primary School 23 Rambatan in using the canva application as a social studies learning media.. Method. This article uses descriptive qualitative research methods, th e steps of which are by going directly to the field and looking for natural data sources, so that the data obtained is accurate and meets the desired results. Results. The result of this study is that the canva application is very suitable for use as a learning media for students of Primary School 23 Rambatan because the media is attractive and able to increase students' enthusiasm for learning. Conclusion. Creating designs with Canva In providing teaching materials for students, for example, such as designs in the form of education in order to attract the attention of students to be interested in seeing the content created.